DEMOKRASI TERPIMPIN SEBUAH KONSEPSI PEMIKIRAN SOEKARNO TENTANG DEMOKRASI - Himawan Indrajat (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2016)
This study analyze about a democracy concept which is developed by President Soekarno in 1950-1959, in that era is implementation parliamentary democracy in Indonesia. President Soekarno disappointment on the implementation parliamentary democracy was state in his spech which titled “Menyelematkan Republik Proklamasi” on febuary 21st 1957, Soekarno gave an idea named President Concept. It said that the experienced during 11 years with liberal or was not suitable with Indonesian personality. Because liberal democracy is import from the west. And in this sistem there is a known term about opposition. This term makes Indonesia suffered because it translate into contra with all goverment policy. The proper kabinet for Indonesia is gotong royong kabinet which consist off all people element, not like kabinet in parliamentary democracy. In his previous speech at general meeting “Merah Putih” Soekarno gaven a clue and tell his ambition to take a part to the goverment before constituent assembly finishe the new constitution. Soekarno also said that he will give the consept which is possible for him to take part in goverment although Indonesia still used parliamentary democracy. Beside the dissapointment of implementation liberal or parliamentary democracy, he also dissapointed because his position as President is only symbol. As we know that indonesia goverment sistem has change on november 14th November 1945 from presidentialism in to parliamentary sistem, as an effort to show Soekarno-Hatta goverment is not a japan puppet. And the impact the position Soekarno as president changed not as a head of goverment but as a head of state. The position head of goverment is in prime minister. Based on the issue that makes Soekarno create a democracy concept which is appropriate with the personality of Indonesia people and an effort Soekarno to restore his legitimacy and authority as a president.